Determinants of day care teachers' job satisfaction - Kusma, Bianca; Groneberg, David A; Nienhaus, Albert; Mache, Stefanie (Central European journal of public health, 2012)
BACKGROUND: Although job satisfaction is among the most widely researched topics, relatively little research has been done on this issue as it relates to early childhood educators. This study was designed to contribute significantly to the deficient body of knowledge about working conditions and job satisfaction of day care teachers, in particular with regard to differences in job satisfaction depending on day care centres' ownership. METHODS: Analyses were based on cross-sectional comparison of 469 questionnaires (42.55% response rate) from day care teachers working at public day care centres with those working at day care centres run by churches or parents' initiatives. RESULTS: A significant difference in job satisfaction was found between these three types. The important interaction between socio-demographic characteristics, psychosocial working conditions, and job satisfaction could be demonstrated. CONCLUSION: The present study is one of the few that examines the impacts of day care centres ownership on pedagogical staffs' job satisfaction and indicates that the type of the centre is a potential factor explaining variations. Results provide a valuable basis for the development of solution-focused approaches to improve pedagogical staff working conditions.
Keywords: personální rozvoj; zařízení denní péče pro děti; pracovní zátěž; sebeuplatnění; Humans; lidé středního věku; dítě; socioekonomické faktory; Child; Self Efficacy; dospělí; Staff Development; věkové faktory; lidé; Socioeconomic Factors; Adult; Faculty; Workload; akademický sbor; Middle Aged; Ownership; Child Day Care Centers; Cross-Sectional Studies; Age Factors; vlastnictví; průřezové studie; pracovní uspokojení; Job Satisfaction